Temporal Variability in Predator–Prey Relationships of a Forest Floor Food Web - McLaughlin, Órla B.; Jonsson, Tomas; Emmerson, Mark C. (Advances in Ecological Research, 2010)
Connectance webs represent the standard data description in food web ecology, but their usefulness is often limited in understanding the patterns and processes within ecosystems. Increasingly, efforts have been made to incorporate additional, biologically meaningful, data into food web descriptions, including the construction of food webs using data describing the body size and abundance of each species. Here, data from a terrestrial forest floor food web, sampled seasonally over a 1-year period, were analysed to investigate (i) how stable the body size–abundance and predator–prey relationships of an ecosystem are through time and (ii) whether there are system-specific differences in body size–abundance and predator–prey relationships between ecosystem types.